Implementation of a water level monitoring prototype in the Viñas reservoir in the city of Pampas in the province of Tayacaja - Pari Huaman , Daniel (2022)
In the present paper, a prototype was developed for the control and monitoring of the water level in the Viñas de Pampas-Tayacaja reservoir. For the development of the prototype, the Arduino UNO board and the HC-SR04 ultrasound sensor were used as main devices; the HC-SR04 sensor allowed to determine the differential of the volume of water deposited in the reservoir. With respect to the development of the graphical interface for monitoring the water level, the mBlock software was used, characterized by its ease of development of very friendly applications; Likewise, a model was built that simulates the reservoir of Viñas del Valle de Pampas, where tests of the operation of the prototype have been carried out. The present paper was developed following the four steps of problem solving: understanding of the problem, plan of activities, execution of activities and test or evaluation of the solution, in the course of Information Management with students of II cycle of the career of industrial engineering.